2021
DOI: 10.1016/j.cmi.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody dynamics and B-cell memory response over time in COVID-19 convalescent subjects

Abstract: Objectives Worldwide spread of COVID-19 disease highlights the need for assessment of long-term humoral immunity in convalescent subjects. Our objectives were to evaluate long-term IgG SARS-CoV-2 antibody response and B-cell memory response in COVID-19 convalescent subjects. Methods Blood samples were collected from a cohort of subjects recovering from COVID-19 disease and from healthy subjects that donated blood. SARS-CoV-2 IgG antibodies were quantitatively detected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
27
2
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 20 publications
8
27
2
3
Order By: Relevance
“…In this study, we found that there were no differences in age, gender, and disease stages in antibody responses. This result is consistent with the previous longitudinal study [12,34,35]. Seropositivity rate (99.5%) was found at 6 months after infection [12], and 95.8% was identified in the follow-up 10 months after infection [13].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that there were no differences in age, gender, and disease stages in antibody responses. This result is consistent with the previous longitudinal study [12,34,35]. Seropositivity rate (99.5%) was found at 6 months after infection [12], and 95.8% was identified in the follow-up 10 months after infection [13].…”
Section: Discussionsupporting
confidence: 92%
“…Repeated paired analyses of the level of IgG antibodies to SARS-COV-2 showed that after 6 and 9 months, only 15.3 % (9 of 59) and 15.8 % (3 of 19) of subjects became seronegative to SARS-COV-2 IgG, respectively. It is noteworthy that all those seronegative showed low levels of antibodies as early as 3 months after the disease [2]. Similar data can be found in other reports [7,9,11].…”
supporting
confidence: 90%
“…This is similar to most case series and small cohort studies of patients with CNS demyelinating disorders around the world (5-8). However, it is drastically lower than the >90% seropositivity within the first 6 months post-infection in the general population and the 76-80% observed in two recent international cohorts (1,3,9,10,15). As we observed a lower seropositivity rate in patients not on a Prior COVID-19 infection severity, patient characteristics, and durations between infection and antibody collection are listed above for patients found to have a persistently positive COVID-19 IgG over time.…”
Section: Discussioncontrasting
confidence: 60%
“…Several studies have demonstrated both humoral and cellular immunity are formed after COVID-19 infection in >90% of the general population, although the duration remains debated (1)(2)(3)(4). Patients with multiple sclerosis (MS) and other CNS demyelinating disorders have been found in cohort studies to have an average rate of post-infection seropositivity between 41 and 80% (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%